TLR2−/− Mice Display Decreased Severity of Giardiasis via Enhanced Proinflammatory Cytokines Production Dependent on AKT Signal Pathway - Li, Xin; Zhang, Xichen; Gong, Pengtao; Xia, Feifei; Li, Ling; Yang, Zhengtao; Li, Jianhua (Frontiers in Immunology, 2017)
Giardia infection is one of the most common causes of waterborne diarrhoeal disease in a wide array of mammalian hosts, including humans globally. Although numerous studies have indicated that adaptive immune responses are important for Giardia defense, however, whether the host innate immune system such as TLRs recognizes Giardia remains poorly understood. TLR2 plays a crucial role in pathogen recognition, innate immunity activation and the eventual pathogen elimination. In the present study, we investigated the role of TLR2 as a non-protective inflammatory response on controlling the severity of giardiasis. RT-PCR analysis suggested that TLR2 expression was increased in vitro. We demonstrated that G. lamblia induced cytokines expression by the activation of p38 and ERK pathways via TLR2. Interestingly, the expression of IL-12 p40, TNF-α, and IL-6, but not IFN-γ, was enhanced in TLR2-blocked and TLR2-/- mouse macrophages exposed to G. lamblia trophozoites compared with WT mouse macrophages. Further analysis demonstrated that G. lamblia trophozoites reduced cytokines secretion by activating AKT pathway in Wild Type (WT) mouse macrophages. Immunohistochemical staining in G. lamblia cysts infected TLR2-/- and WT mice showed that TLR2 was highly expressed in duodenum in infected WT mice. Also, infected TLR2-/- and AKT-blocked mice showed an increased production of IL-12 p40 and IFN-γ compared with infected WT mice at the early stage during infection. Interestingly, infected TLR2-/- and AKT-blocked mice displayed a decreased parasite burden，an increased weight gain rate and short parasite persistence. Histological morphometry showed shortened villus length, hyperplastic crypt and decreased ratio of villus height/crypt depth in infected WT mice compared with in infected TLR2-/- and AKT-blocked mice. Together, our results suggested that TLR2 deficiency lead to alleviation of giardiasis and reduction of parasite burden through the promotion of proinflammatory cytokines production. For the first time our results demonstrated that TLR2 played a negative role in host defense against Giardia. Keywords: Giardia, giardiasis, TLR2, TLR2-/-, AKT, cytokines.